2015
DOI: 10.1140/epjst/e2015-02350-4
|View full text |Cite
|
Sign up to set email alerts
|

Controlling quantum critical dynamics of isolated systems

Abstract: Abstract. Controlling the non adiabatic dynamics of isolated quantum systems driven through a critical point is of interest in a variety of fields ranging from quantum simulation to finite-time thermodynamics. We briefly review the different methods for designing protocols which minimize excitation (defect) production in a closed quantum critical system driven out of equilibrium. We chart out the role of specific driving schemes for this procedure, point out their experimental relevance, and discuss their impl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 151 publications
(240 reference statements)
0
44
0
Order By: Relevance
“…A class of such dynamical phenomenon involve periodically driven quantum systems leading to multiple passages through their critical points during a drive cycle [18][19][20][21][22] . Such systems exhibit a wide class of dynamical phenomena which do not occur in their aperiodically driven counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A class of such dynamical phenomenon involve periodically driven quantum systems leading to multiple passages through their critical points during a drive cycle [18][19][20][21][22] . Such systems exhibit a wide class of dynamical phenomena which do not occur in their aperiodically driven counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, periodically driven integrable systems show a separate class of dynamical transitions which originates from the change in topology of their Floquet spectrum and leaves its imprint on temporal behavior of local correlation functions 24 . Such driven systems also exhibit the phenomenon of dynamics induced freezing 21,22,25,26 ; this phenomenon manifests itself in a near unity overlap of the system wavefunction after single or multiple drive period(s) with the initial wavefunction at t = 0. Such near-unity overlap signifying freezing occurs at specific discrete frequencies ω * and is therefore qualitatively different from the trivial freezing that occurs for ultrafast drive frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that even when the spectral properties are available, the required control fields to guide the dynamics of a complex system involves highly nonlocal interactions. This understanding has been gained by analyzing critical quantum spin systems [77][78][79][80][81][82][83][84], see [3] for a review.…”
Section: Many-body Systems: Complexity Barriermentioning
confidence: 99%
“…In addition, theoretical studies have shown that STA can be used to guide the evolution of many-body quantum systems that exhibit quantum critical behavior [30,31]. In this context, STA can be used to suppress excitation formation across a phase transition [32]. Implementing STA may require modifying the systems Hamiltonian with nonlocal interactions including high order terms [30,33].…”
Section: Introductionmentioning
confidence: 99%